2018
DOI: 10.3390/app8091578
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Crossing Cache Placement in Cache-Enabled Device to Device-Aided Cellular Networks

Abstract: In cache-enabled device-to-device (D2D) -aided cellular networks, the technique of caching contents in the cooperative crossing between base stations (BSs) and devices can significantly reduce core traffic and enhance network capacity. In this paper, we propose a scheme that establishes device availability, which indicates whether a cache-enabled device can handle the transmission of the desired content within the required sending time, called the delay, while achieving optimal probabilistic caching. We also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In the literature, there have been many studies on the content caching strategies in D2D networks. For instance, an optimal content caching approach was proposed in [10] to maximize offloading probability with effective transmission accessibility between devices. In [13], the authors studied a probabilistic caching placement strategy for stochastic D2D caching networks, and obtained the optimal caching probabilities that maximize the requests successfully served by local device caches.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there have been many studies on the content caching strategies in D2D networks. For instance, an optimal content caching approach was proposed in [10] to maximize offloading probability with effective transmission accessibility between devices. In [13], the authors studied a probabilistic caching placement strategy for stochastic D2D caching networks, and obtained the optimal caching probabilities that maximize the requests successfully served by local device caches.…”
Section: Related Workmentioning
confidence: 99%
“…For example, content requests can be offloaded from a base station (BS) by caching received contents in user devices and fulfilling other nearby requests via D2D forwarding. Device caching strategies are investigated in [8]- [10], assuming that D2D users are cooperative and willing to cache a video that is not requested by themselves. Social-awareness is further taken into account in [11], [12], so that D2D users are more incentivized to cache and forward contents for their social connections.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on D2D networks have focused on different aspects of the caching placement policy to improve the efficiency of cache [14][15][16][17][18]. The authors of [14] showed an optimal caching placement scheme to maximize the offloading probability with considering the impact of transmission device availability.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies on D2D networks have focused on different aspects of the caching placement policy to improve the efficiency of cache [14][15][16][17][18]. The authors of [14] showed an optimal caching placement scheme to maximize the offloading probability with considering the impact of transmission device availability. In [15], the authors described a probabilistic caching placement scheme that takes the cacheaided throughput into account; it measures the density of successfully served requests through own local cache of the user or through its nearby devices via D2D transmission.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation